TINJAUAN KUALITATIF EFEKTIVITAS KAHOOT SEBAGAI MEDIA EVALUASI DALAM MEMPERKUAT PEMAHAMAN KONSEP SISWA SMAN 15 GARUT (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of Kahootas an evaluation tool in strengthening students’ conceptual understanding at SMAN 15 Garut. Thisresearch employs a qualitative approach using a literature study method by reviewing various relevantsources such as scientific journals, books, andresearch articles related to digital-based evaluationmedia in learning. Data collection techniques were conducted through content analysis of selectedliterature, while data analysis was carried out bycategorizing, comparing, and interpreting findings fromprevious studies. The results indicate that Kahoot is aneffective evaluation tool in enhancing studentengagement, motivation, and conceptualunderstanding. Its strengths lie in providing immediatefeedback, creating an interactive learning environment, and encouraging active student participation throughgamification elements. However, several limitationswere identified, including dependency on internet access, limited technological devices, and thetendency of students to prioritize speed over deepunderstanding. The effectiveness of Kahoot is alsoinfluenced by several factors, such as the quality ofquestion design, teacher implementation strategies, and students’ technological readiness. Therefore, theuse of Kahoot should be carefully designed to ensurethat it not only increases motivation but alsostrengthens students’ conceptual understanding. In conclusion, Kahoot can serve as an innovative andrelevant evaluation tool to support 21st-century learning.